Student's Behavioral Abnormalities in Markazi and Hamedan Provinces - Hossein Salimi-Bajestani; Mojtaba Mohammadi-Jalali Farahani; Ali Delavar; Kiumars Farahbakhsh; Abdullah Motamedi; Reza Saki (Shahid Beheshti University of Medical Sciences, 2018)
Background and objectives: Behavioral anomalies in the behavior of a person with social values are defied as the extent of the inconsistency. Since students are the future managers of community behavioral health Therefore, it seems necessary. The purpose of this research is to develop the student's behavior anomalies Atlantic and central provinces of Hamedan. Material and methods: This study is the objective, functional, and due to a combination of survey methods and causal comparative. Using a standard questionnaire forms Aachen Bach TRF and YSR were collected. The data in the fild and independent groups't-test was used in the content analysis of qualitative analysis. Results: The results showed that the prevalence of behavioral disorders in the Markazi and Hamadan provinces are different (t=13.42, P>0.0001). The results showed that the prevalence of behavioral disorders in boys and girls was not a signifiant difference (t=-1.50, P<0.05). Conclusion: The prevalence of behavioral disorders in different groups according to sex, age and place of residence is different.